Analisis Materi Aritmetika Sosial Menggunakan Konteks Literasi Finansial - Pakpahan, Theresia Feby; Retta, Allen Marga; Nopriyanti, Tika Dwi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2023)
This study aims to analyze the material of social arithmetic using the context of financial literacy. The research was conducted at SMP Negeri 2 Lubuk Besar. Data was collected by combining the results of student learning tests and interviews. Interviews were conducted to support the test results that have been obtained and are associated with learning on social arithmetic material using the context of financial literacy. The data analysis techniques used are: 1) data reduction; 2) data presentation; 3) drawing conclusions. The results showed that: 1) the arithmetic material using the context of financial literacy affects the results of the learning test; 2) social arithmetic material using the context of financial literacy influences students' decision making; 3) the number of students with good decision making is more than the number of students with poor decision making.